Finance and Development, March 1987. (Finance and Development; Finance and Development ;, 1987)
The issue of capital flight from developing countries is discussed. The debt problems of developing countries coupled with the sharp decline in international lending to many countries have evoked great interest in the issue of private capital outflows, or capital flight, from these countries among international policymakers, academics, and in the general public. Residents of countries with exchange controls can purchase foreign exchange overseas by paying in local currencies, albeit at a higher cost than through official channels.